Registros notables de la guacamaya verde (ara militaris) en el norte del estado de Guerrero, México - Villaseñor, Emma; Botello, Francisco (Instituto de Ecología, A.C., 2012)
We report for first time the presence of military macaw (Ara militaris) in the north region of Guerrero State. The region is not considered in any conservation instrument, and this report highlights the urgent need for conservation planning in the state.